Protection Factors on Adolescent Mental Health Condition due to Pandemic COVID-19 - Rr Setyawati (UM Purwokerto Press, 2021)
This pandemic has brought some impacts such as physical, psychological, social, and economic (Poudel & Subedi, 2020). Until now, all parties say that they have not found a way to overcome it because of the extreme situation that has never happened before. Empirical studies on the impact of the health crisis on physical, and mental health have become a priority to solve these arising problems (Schimmenti et al., 2020). Lockdown can affect the mental health of adolescents. The impact of lockdown or activity restriction can cause psychological stress on adolescents (Chen et al., 2020). Teens are supposed to be cut off from peers and school as everyone worries about illness and about their future which are beyond their control (Singh et al., 2020) Therefore this paper tries to contribute to overcoming these problems, especially in the adolescent age group. Basically, teenagers have creative potential, resilience, and resourceful, especially if they have supportive adults in their lives. Parents or adults around them need to talk with teenagers about their experiences during the Covid 19 pandemic and talk about any support they might need. Parents can help teenagers create a structure or activity plan during the Covid 19 pandemic. Although this plan may not be desirable at this time, it is something that is needed. Basically, teenagers need help to create and develop their strength and ability. Parents can help adolescents to build relationships with mental health resources either through school or in the community. They can set an example by finding healthy coping skills, such as meditation, peer support, counseling, and exercise.